Sociopreneurship in Ecotourism: Strengthening Village Economies Around Tanjung Puting National Park - Harinie, Luluk Tri; Sukmani, Meylinda; Romadoni, Muhamad; Bancin, John Budiman (Humaniora: Journal of Indonesia Culture and Society, 2025)
Tanjung Puting National Park (TNTP) in Central Kalimantan is an internationally recognized ecotourism destination that significantly contributes to national revenue and plays a crucial role in shaping regional socioeconomic development. This research examines the role of sociopreneurship in promoting the economic sustainability of rural communities through ecotourism development, focusing on Bahaur Village and Pembuang Hulu I Village, both of which maintain a direct connection to the TNTP area. A qualitative case study approach is employed, combining participant observation, in-depth interviews with ten key informants (including village heads, secretaries, freshwater fish farming group leaders, and community figures), and an analysis of village deliberation documents. Data analysis follows three main stages—intuition, analysis, and description—supported by a SWOT framework to identify strengths, weaknesses, opportunities, and threats. To ensure data validity, triangulation is applied by comparing and cross-verifying information from interviews, observations, and documents to identify consistent patterns and reduce potential bias. The findings indicate that although ecotourism has the potential to increase local income, it has not yet effectively strengthened community-based business development. The primary challenges include weak infrastructure, limited training opportunities, and inadequate marketing strategies, which have compelled some residents to revert to environmentally harmful economic activities. The implications underscore the need for strategic planning, capacity building, mentoring, market access facilitation, and multi-stakeholder collaboration to diversify the local economy and sustain community enterprises within conservation areas.